APMAP interacts with lysyl oxidase–like proteins, and disruption of Apmap leads to beneficial visceral adipose tissue expansion. Issue 9 (19th September 2017) - Pessentheiner, Ariane R.; Huber, Katharina; Pelzmann, Helmut J.; Prokesch, Andreas; Radner, Franz P. W.; Wolinski, Heimo; Lindroos‐Christensen, Josefine; Hoefler, Gerald; Rülicke, Thomas; Birner‐Gruenberger, Ruth; Bilban, Martin; Bogner‐Strauss, Juliane G.
ABSTRACT: Adipocyte plasma membrane–associated protein (APMAP) has been described as an adipogenic factor in 3T3‐L1 cells with unknown biochemical function; we therefore aimed to investigate the physiologic function of APMAP in vivo. We generated Apmap‐knockout mice and challenged them with an obesogenic diet to investigate their metabolic phenotype. We identified a novel truncated adipocyte‐specific isoform of APMAP in mice that is produced by alternative transcription. Mice lacking the full‐length APMAP protein, the only isoform that is expressed in humans, have an improved metabolic phenotype upon diet‐induced obesity, indicated by enhanced insulin sensitivity, preserved glucose tolerance, increased respiratory exchange ratio, decreased inflammatory marker gene expression, and reduced adipocyte size. At the molecular level, APMAP interacts with the extracellular collagen cross‐linking matrix proteins lysyl oxidase–like 1 and 3. On a high‐fat diet, the expression of lysyl oxidase–like 1 and 3 is strongly decreased in Apmap‐knockout mice, paralleled by reduced expression of profibrotic collagens and total collagen content in epididymal white adipose tissue, indicating decreased fibrotic potential. Together, our data suggest that APMAP is a novel regulator of extracellular matrix components, and establish that APMAP is a potential target to mitigate obesity‐associated insulin resistance.—Pessentheiner, A. R., Huber, K., Pelzmann, H. J., Prokesch, A., Radner, F. P. W., Wolinski, H., Lindroos‐Christensen, J., Hoefler, G., Rülicke, T., Birner‐Gruenberger, R., Bilban, M., Bogner‐Strauss, J. G. APMAP interacts with lysyl oxidase–like proteins, and disruption of Apmap leads to beneficial visceral adipose tissue expansion. FASEB J. 31, 4088–4103 (2017). www.fasebj.org —Pessentheiner, Ariane R., Huber, Katharina, Pelzmann, Helmut J., Prokesch, Andreas, Radner, Franz P. W., Wolinski, Heimo, Lindroos‐Christensen, Josefine, Hoefler, Gerald, Rülicke, Thomas, Birner‐Gruenberger, Ruth, Bilban, Martin, Bogner‐Strauss, Juliane G. APMAP interacts with lysyl oxidase–like proteins, and disruption of Apmap leads to beneficial visceral adipose tissue expansion. FASEB J. 31, 4088–4103 (2017)